Functional testing in animal models of spinal cord injury: not as straight forward as one would think - Fouad, Karim; Hurd, Caitlin; Magnuson, David (Frontiers in Integrative Neuroscience, 2013)
When exploring potential treatments for spinal cord injury (SCI), functional recovery is deemed the most relevant outcome measure when it comes to translational considerations. Yet, assessing such recovery and potential treatment effects is challenging and the pitfalls are frequently underestimated. The consequences are that in many cases positive results cannot be reliably replicated, and likely treatments that appear to lack effects have been dismissed prematurely. In this article we review the relationships between lesion location/severity and functional outcomes with specific consideration given to floor and ceiling effects. The roles of compensatory strategies, the challenges of distinguishing them from bona fide recovery, and of comparing function to pre-injury levels given the variability inherent in animal testing are discussed. Ultimately, we offer a series of considerations to enhance the power of functional analysis in animal models of SCI.